Morphological and genetic identification of yeasts from skin and oral infection in children in the Basrah province - AL-Mosawi, Fatima T. M.; Abu-Mejdad, Najwa M. J. A.; Al-Hilfi, Athraa A. A. (Rzeszów University Press, 2025)
Introduction and aim. Human fungus infections are widespread and can lead to a variety of diseases in children. The purpose of this study was to isolate and identify yeasts from various places in children, including skin (diaper area) and oral cavity, utilizing morphological and molecular approaches for precise categorization. Material and methods. One hundred swabs were collected from children clinically diagnosed with fungal skin infections. The isolated yeast species were examined, purified, and morphologically. The sequences have been deposited in GenBank of Japan as new strains under accession numbers LC790886 to LC79098. including Candida albicans, Pichia kudriavzevii, Magnusiomces capitatus, Nakaseomyces glabratus, Kluyveromyces marxianus, Candida tropicalis, Meyerozyma guiliermonolii, Clavispora lusitaniae, Candida parapsilosis, Trichosporon ashii. The isolates were cultured on Sabouraud Dextrose Agar with chloramphenicol, and species identification was carried out using CHROMagar Candida medium and lactophenol cotton blue staining. Molecular identification was performed using PCR amplification of the ITS1-5.8S-ITS2 rDNA region, followed by DNA sequencing. Results. The presence of 10 yeast species, with C. albicans 56% representing the highest percentage of these, while the percentage of other yeasts was 44%. The Candida species was found to have the highest percentage of occurrence, 58% followed by the C. tropicalis species, 19%, which had a lower percentage of occurrence. Conclusion. The phenotypical and genetic characteristics of yeast have been identified by the use of clinically isolated samples of children.
Before participating in the trial, each participant gave his informed consent. In November 2022, the Ethics Committee of 1165 accepted the protocol and the study was carried out in accordance with the Declaration of Helsinki.
Keywords: Candida; newborns; oral candidiasis; skin infection